Paz, narcotráfico y violencia: ¿década perdida? (2020)
Peace talks between the FARC guerrilla and the Colombian State began in 2012. Such a scenario gave rise to think of an upcoming period in which rural inhabitants could work and live in an environment free of violence, which would lead to an improvement in their socioeconomic conditions. In 2016, with the signing of the Peace Agreement, the negotiations came to an end. However, at the time of the post-agreement, given the poor actions of the Colombian State to recover the afflicted territories, the suspension of the aerial spraying of glyphosate and the active presence of a fraction of the guerrilla that did not join the demobilization contemplated in the Peace Agreement, enough conditions were given for dissidents and other criminal organizations to take over the territories previously dominated by the FARC and to become main actors in the illegal drug trafficking economy. Thus, there was a considerable increase in illicit crops used to finance criminal activities associated with drug trafficking. This research seeks to explore how the repressive actions of the State against drug trafficking and those of the new criminal actors have victimized the rural population in the departments of Nariño, Norte de Santander, and Putumayo within the period 2010-2018. The discussion arises around these three departments as they present the highest density of illicit crops and armed groups within their territories. This essay addresses the relationship between the number of people who are victims of the armed conflict, the intensity of the State fight against drugs, illicit crops, GDP, demography, and population.